Phubbed and Furious: Narcissists’ Responses to Perceived Partner Phubbing - Claire M. Hart; Katherine B. Carnelley; Laura M. Vowels; Tessa Thejas Thomas (Behavioral Sciences)
We conducted a diary study to examine how narcissism influences reactions to daily perceived partner phubbing (N = 196). We examined relationships between two facets of narcissism (rivalry and admiration) and personal and relational well-being, reactions to phubbing, reports of retaliation, and motives for retaliation. On average, participants higher in rivalry reported lower self-esteem and higher depressed and anxious mood, whilst participants higher in admiration reported greater relationship satisfaction, higher self-esteem, lower depressed and anxious mood, and lower levels of anger/frustration. These patterns held regardless of whether they were phubbed or not. In response to partner phubbing, participants higher in rivalry reported, on average, greater curiosity, resentment, conflict, and retaliation. On days when participants reported higher phubbing, those with higher rivalry reported greater curiosity, while those higher in admiration reported greater conflict. When retaliating to phubbing, those higher in rivalry did so, on average, to get back at their partner and to seek support and approval from others, whereas those higher in admiration were less likely to report boredom as a reason for retaliating. Our findings contribute to the sparse literature on narcissism and phubbing by showing how narcissists respond to being phubbed. We discuss how phubbing may exacerbate their relational difficulties.